2006
DOI: 10.1002/nme.1651
|View full text |Cite
|
Sign up to set email alerts
|

A stabilized nodally integrated tetrahedral

Abstract: SUMMARYA stabilized, nodally integrated linear tetrahedral is formulated and analysed. It is well known that linear tetrahedral elements perform poorly in problems with plasticity, nearly incompressible materials, and acute bending. For a variety of reasons, low-order tetrahedral elements are preferable to quadratic tetrahedral elements; particularly for nonlinear problems. But the severe locking problems of tetrahedrals have forced analysts to employ hexahedral formulations for most nonlinear problems. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
207
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(212 citation statements)
references
References 20 publications
3
207
0
2
Order By: Relevance
“…For these reasons, even if the traditional FEM provides very good results in many applications, alternative techniques based on modified FEM formulations or on meshfree approximation schemes [10] appear an interesting alternative in the simulation of metal forming processes. Recently it has been shown that the application of nodal integration techniques to the FEM makes the method insensitive to mesh distortion and alleviates volumetric locking problems in the study of incompressible materials [11][12][13]. Thanks to this features the nodal integrated FEM appears particularly suited for metal forming and machining problems; however its application is still in the process of development [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, even if the traditional FEM provides very good results in many applications, alternative techniques based on modified FEM formulations or on meshfree approximation schemes [10] appear an interesting alternative in the simulation of metal forming processes. Recently it has been shown that the application of nodal integration techniques to the FEM makes the method insensitive to mesh distortion and alleviates volumetric locking problems in the study of incompressible materials [11][12][13]. Thanks to this features the nodal integrated FEM appears particularly suited for metal forming and machining problems; however its application is still in the process of development [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…First, to achieve the same solution, accuracy for a given FE analysis requires far more tetrahedral elements then hexahedral elements, and this leads to higher computational costs (both time and memory) [6,21]. Even more, when the aim is to apply FE analysis, tetrahedral meshes produce acceptable displacement results but are relatively inaccurate for predicting stresses [18,20]. Hexahedral mesh generation is constrained by the need to decompose a desired geometry (repeatedly) into simpler sub-geometries that can be meshed automatically [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, there has been renewed efforts to remedy the poor performance of low-order triangular and tetrahedral finite elements in the near-incompressible regime [41,42,43,44,45,46,47,48]. These approaches are broadly based on the idea of reducing the number of incompressibility constraints by defining nodal-averaged pressures or strains.…”
Section: Introductionmentioning
confidence: 99%
“…[48], a special form of a nodal strain matrix was computed from the elements attached to the node, and it led to a locking-free displacement-based formulation. Although these nodal methods tend not to lock, several authors have reported pressure oscillations for highly constrained problems [45,46].…”
Section: Introductionmentioning
confidence: 99%